VD_FINDINFO HC / 2019 / 58 vom 6. Februar 2019 - VD Tribunal cantonal (2019)
OBLIGATION D'ENTRETIEN, MAJORITÉ{ÂGE}, MAXIME INQUISITOIRE, MAXIME OFFICIELLE | 277 al. 2 CC, 58 al. 1 CPC (CH), 58 al. 2 CPC (CH)